2020
DOI: 10.1371/journal.pone.0230901
|View full text |Cite
|
Sign up to set email alerts
|

PET segmentation of bulky tumors: Strategies and workflows to improve inter-observer variability

Abstract: Background PET-based tumor delineation is an error prone and labor intensive part of image analysis. Especially for patients with advanced disease showing bulky tumor FDG load, segmentations are challenging. Reducing the amount of user-interaction in the segmentation might help to facilitate segmentation tasks especially when labeling bulky and complex tumors. Therefore, this study reports on segmentation workflows/strategies that may reduce the inter-observer variability for large tumors with complex shapes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 40 publications
1
17
0
2
Order By: Relevance
“…However, no single semi-automated delineation method, including MV3 performs optimally for different types of lymphoma at different therapeutic stages without the need for manual correction (25). Therefore a workflow where observers select the visually best performing method per lesion might improve overall delineation success while minimizing interobserver variability compared to manual segmentation (36). Translating this workflow at I-PET DBLCL might imply that lesions with SUVmax<10 should be delineated using method MV3 and that lesions with SUVmax>10 should be delineated using method SUV4.0, or only in case observers consider MV3 contouring as failed.…”
Section: Discussionmentioning
confidence: 99%
“…However, no single semi-automated delineation method, including MV3 performs optimally for different types of lymphoma at different therapeutic stages without the need for manual correction (25). Therefore a workflow where observers select the visually best performing method per lesion might improve overall delineation success while minimizing interobserver variability compared to manual segmentation (36). Translating this workflow at I-PET DBLCL might imply that lesions with SUVmax<10 should be delineated using method MV3 and that lesions with SUVmax>10 should be delineated using method SUV4.0, or only in case observers consider MV3 contouring as failed.…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, highly recommended to keep the level of user interaction as low as possible, as we recently showed in Ref. [44]. By using a semi‐automated segmentation approach and workflow, which required delineation adjustment in a few cases (when the tumor was located to another high‐uptake region), we tried to limit the amount of user interaction and we found that this reduces the observer variability as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Although tumor segmentation and feature extraction are essential parts of -omics prediction, they are not integrated into a single model. Consequently, such -omics methods are hardly reproducible in other institutions [17][18][19][20]. Therefore, it is necessary to deal with radiological and radiotherapy images themselves, instead of radiomics and dosiomics.…”
Section: Introductionmentioning
confidence: 99%